Differential roles of Cassia tora 1-deoxy-D-xylulose-5-phosphate synthase and 1-deoxy-D-xylulose-5-phosphate reductoisomerase in trade-off between plant growth and drought tolerance - Tian, Chunyao; Quan, Huige; Jiang, Ruiping; Zheng, Qiaomu; Huang, Sipei; Tan, Guodong; Yan, Chaoyue; Zhou, Jiayu; Liao, Hai (Frontiers in Plant Science, 2023)
Due to global climate change, drought is emerging as a major threat to plant growth and agricultural productivity. Abscisic acid (ABA) has been implicated in plant drought tolerance, however, its retarding effects on plant growth can not be ignored. The reactions catalyzed by 1-deoxy-D-xylulose-5-phosphate synthase (DXS) and 1-deoxy-D-xylulose-5-phosphate reductoisomerase (DXR) proteins are critical steps within the isoprenoid biosynthesis in plants. Here, five DXS (CtDXS1-5) and two DXR (CtDXR1-2) genes were identified from Cassia tora genome. Based on multiple assays including the phylogeny, cis-acting element, expression pattern, and subcellular localization, CtDXS1 and CtDXR1 genes might be potential candidates controlling the isoprenoid biosynthesis. Intriguingly, CtDXS1 transgenic plants resulted in drought tolerance but retardant growth, while CtDXR1 transgenic plants exhibited both enhanced drought tolerance and increased growth. By comparison of β-carotene, chlorophyll, abscisic acid (ABA) and gibberellin 3 (GA3) contents in wild-type and transgenic plants, the absolute contents and (or) altered GA3/ABA levels were suggested to be responsible for the balance between drought tolerance and plant growth. The transcriptome of CtDXR1 transgenic plants suggested that the transcript levels of key genes, such as DXS, 9-cis-epoxycarotenoid dioxygenases (NCED), ent-kaurene synthase (KS) and etc, involved with chlorophyll, β-carotene, ABA and GA3 biosynthesis were induced and their contents increased accordingly. Collectively, the trade-off effect induced by CtDXR1 was associated with redesigning architecture in phytohormone homeostasis and thus was highlighted for future breeding purposes.